2001
DOI: 10.1046/j.1439-0426.2001.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability, growth and external morphology of meiotic- and mitotic-gynogenetic diploids in red sea bream, Pagrus major

Abstract: Two types of gynogenetic diploids were arti®cially induced in the red sea bream (Pagrus major Temminck et Schlegel), either by suppressing the ®rst cell cleavage (mitotic-G2N) or by retaining the second polar body (meiotic-G2N). The eggs of red sea bream were inseminated with UV-irradiated (3000 erg mm )2 ) sperm of Japanese parrot ®sh (Oplegnathus fasciatus Temminck et Schlegel), and hydrostatic pressure shock of 700 kg cm )2 for 5.5 min at 46 min after insemination (mitotic-G2N) and cold shock of 1°C for 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Similar results for red sea bream were described by Kato et al. (). A lower survival rate was observed in gynogenetic red sea bream juveniles (1–90 dph) fed Branchinous sp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results for red sea bream were described by Kato et al. (). A lower survival rate was observed in gynogenetic red sea bream juveniles (1–90 dph) fed Branchinous sp.…”
Section: Discussionsupporting
confidence: 91%
“…Thus far, similar feeding experiments of chromosome manipulated fish were described for only few teleost such as red sea bream Pagrus major , sea bass Dicentrarchus labrax L., and honmoroko Gnathopogan caerulescens . It has been observed that gynogenetic diploids of red sea bream (Kato, Murata, Yamamoto, Miyashita, & Kumai, ), plaice Pleuronectes platess L. (Purdom, ), and loach (Suzuki, Oshiro, & Nakanishi, ) are characterized by lower growth rates than normal fish. Colombo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely because of the increased frequencies of some deleteriously homologous recessive genes and lack of paternal DNA in gynogens, which might be essential for larvae to get through the critical stages of early development (Arai 2001;Felip et al 2001). Furthermore, the negative effects of cold stress associated with gynogenesis induction might also lead to the poor survival of diploid gynogens (Kato et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Red sea bream Pagrus major is one of the most important fish cultured in Japan. To improve the traits of this species, breeding experiments, including mass selection, 12 chromosome manipulation 13,14 and sex control 15 have been conducted. To develop transgenic technology in a new species, transgenic expression vectors with transcriptional activity in the species of choice have to be constructed.…”
Section: Introductionmentioning
confidence: 99%